The effects of strategic attributes on organizational performance in the banking sector of Pakistan - Ahmed, Ammar (2018)
In recent times, there has been an increasing interest in the strategic attributes which aims to achieve the superior organizational performance that allows organizations, including the banks, to be competitive with time. Therefore, to achieve superior organizational performance and successful bank growth, the banks need to focus on their strategic attributes. The key strategic attributes include strategic orientation, organizational culture, organizational IMO, and organizational commitment. Drawing upon the resource-based view theory (RBV) and the social exchange theory (SET), this study examined the influence of these strategic attributes on organizational performance. Moreover, this study also examined the mediating effect of organizational commitment on the relationship between strategic orientation, organizational culture, organizational IMO and organizational performance. The data was collected from the 260 bank managers working in the branches of six-large banks of Pakistan. The results of PLS path modeling revealed the significant positive direct relationships between strategic orientation, organizational culture, organizational IMO and organizational commitment, and organizational performance. Similarly, the study also found significant positive direct relationships between strategic orientation and organizational culture, and organizational commitment. However, no significant relationship existed between organizational IMO and organizational commitment. Furthermore, the bootstrapping results revealed that organizational commitment mediated the relationships between strategic orientation, organizational culture, and organizational performance. In contrast, the study did not find any mediation of organizational commitment between organizational IMO and organizational performance relationship. In general, the findings showcased that organizational performance can be enhanced through the examined key strategic attributes of the study. Accordingly, the study has forwarded noteworthy claims regarding the mediating effect of organizational commitment on these variables. The study offers theoretical and practical contributions. This study also highlights the crucial role of these strategic attributes for performance improvement in the banking sector. Lastly, limitations and scope of further studies are also provided.